Introducing and Reviewing the Book The Developments of the Arabic Language from the Beginning up to Now with Statistical Stylistics Approach - Zahra Karamzadegan (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mohammad Khaqani Isfahani, in his book, has used this statistical stylistic function to study the Arabic language and extract high-frequency linguistic forms for use in educational programs. This article, while introducing and examining the form and content of this book, acknowledges that there is no need for the statistical study of Arabic language in the first place. Because of some reasons, classical Arabic has remained unchanged throughout history. On the other hand, using shortcut solutions such as “trust in experience and reading text”, “paying attention to the semantic functions of linguistic forms”, “browsing syntactic books such as Jammu al-Darrow and Qatari al-Wadi al-Sadi's description” and “Referrals that collect syntactic evidence” can be extracted from high-frequency linguistic forms, and necessarily, as the respected author asserts, using the statistical method of time stylization is not the only solution.